(Asymmetric) trade costs, real exchange rate hedging, and equity home bias in a multicountry model. Issue 2 (1st November 2017) - Pyun, Ju Hyun
Abstract: There has been controversy between (two‐country) theory and the empirics about whether hedging against real exchange rate fluctuations in the goods market influences foreign equity holdings. This study reconciles the theory with the empirics by introducing a multicountry framework with asymmetric trade costs. We find that the incentive to hold foreign equities to hedge real exchange rate risk is negligible because multiple trade partners act as a hedging channel for real exchange rate fluctuations. Further, our theory calls for a country's covariance–variance ratio to be constructed as the sum of the bilateral covariance–variance ratios of the multiple partners. The empirical analysis of 24 advanced countries confirms the theoretical prediction.